Historical perspective of Otto Nordenskjöld's Antarctic penguin fossil collection and Carl Wiman's contribution - Acosta Hospitaleche, Carolina Ileana Alicia; Hagström, Jonas; Reguero, Marcelo Alfredo; Mörs, Thomas (Polar Record)
The early explorer and scientist Otto Nordenskjöld, leader of the Swedish South Polar Expedition of 1901-1903, was the first to collect Antarctic penguin fossils. The site is situated in the northeastern region of Seymour Island and constitutes one of the most important localities in the study of fossilised penguins. The task of describing these specimens together with fossilised whale remains was given to Professor Carl Wiman (1867-1944) at Uppsala University, Sweden. Although the paradigm for the systematic study of penguins has changed considerably over recent years, Wiman's contributions are still remarkable. His establishment of grouping by size as a basis for classification was a novel approach that allowed them to deal with an unexpectedly high morphological diversity and limited knowledge of penguin skeletal anatomy. In the past, it was useful to provide a basic framework for the group that today could be used as 'taxon free' categories. First, it was important to define new species, and then to establish a classification based on size and robustness. This laid the foundation for the first attempts to use morphometric parameters for the classification of isolated penguin bones. The Nordenskjöld materials constitute an invaluable collection for comparative purposes, and every year researchers from different countries visit this collection. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Hagström, Jonas. Swedish Museum of Natural History; Suecia Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: ...